Pelatihan dan Pengajaran Implementasi Strategi Pemasaran Digital E-Wom untuk Meningkatkan Jumlah Siswa di Madrasah Tsanawiyah Azzidin Medan Denai - Edy Firmansyah; Arham Syaukani; Dea Okviar Egano Napitupulu; Ficha Aulia Nanda; Ilhamsyah Siregar; Rio Dwi Fikriansyah (Jurnal Pelayanan Masyarakat, 2024)
Madrasah Tsanawiyah Azzidin Medan is a junior high school in Medan Denai District that promotes not only through manual media, but also through social media. However, during the period of 2023, the number of students who want to attend Madrasah Tsanawiyah Azzidin has decreased from 85 students in 2022 to 73 students in 2023. This is because there are still many teachers, education staff and school marketing staff who are unable to convey good and positive communication to prospective consumers through e-wom facilities, so they are less able to give a positive impression when conducting promotions. As a result, promotions with e-wom have not been utilized optimally, which makes parents of students as consumers unable to communicate carefully every message and positive impression through the school, because they still prioritize manual promotions, so that many of these prospective consumers have not been moved, so they decide not to attend Madrasah Tsanawiyah Aidin Medan Denai so that training and teaching are needed regarding the implementation of e-WOM. The method of implementing this training is done by conducting lecture methods, as well as through real presentations and simulations in implementing e-WOM applications on social media to carry out promotional activities in order to increase the number of students attending Madrasah Tsanawiyah Azzidin Medan. From the results of community service in the form of training on implementing e-WOM marketing applications, it can be seen that 37 education personnel, teachers and marketing personnel at Madrasah Tsanawiyah Azzidin Medan can improve their ability to implement the use of e-WOM applications when conducting promotions to increase the number of students who will attend Madrasah Tsanawiyah Azzidin Medan.